PENGARUH KUALITAS ANGGARAN DAN PENGENDALIAN ANGGARAN TERHADAP EFEKTIVITAS ORGANISASI DI LINGKUNGAN PEMERINTAHAN KOTA JAMBI - . Sugiharto (Magister Ilmu Akuntansi Universitas Jambi, 2015)
The research goal is to analyze and demonstrate empirically on Effect of Budget and Budgetary Control Quality Organizational Effectiveness Against Government within the City of Jambi either partially or simultaneously and determine the amount of the impact or effect of the Budget and Budgetary Control Quality Organizational Effectiveness Against Government within the City of Jambi. Techniques or methods used in data collection in the study with the technique or method of purposive random sampling ( purposive sampling / Judgement ) conducted by survey method by distributing research instruments / questionnaires to the respondents with a list of questions / questionnaire , further explanation is given orally, in addition to the also carried out interviews with 39 respondents from the Government on education in the work environment where every SKPDs City of Jambi taken 5 of the respondents as the study sample, obtained from distributing questionnaires or quoestioner with total 195 questionnaire respondents . Distribution of 195 questionnaires , 163 were returned , which can not be processed 32 , and the data that can be processed is 158 questionnaire. Based on calculations of data analysis program SPSS 20 , the description of the results obtained in testing the hypothesis that a partial ( t-test ) , it is known that the partial hypothesis 1.1 which states that the quality of the budget significantly affect the effectiveness of government organizations and the city of Jambi 1.2 hypothesis which states control budget significantly affect organizational effectiveness Jambi city government is evidenced by the value of the t-test at α 0.05 is above 1,725 ​​t count on the quality of budgetary control budgetary 6.670 and 6.195 and simultaneous hypothesis testing ( test - F ) , it is known that simultaneous hypothesis 2 stated that the quality of budget and budgetary control significantly affects organizational effectiveness Jambi city government is proved by the calculated value of the F - test results on α - F 3.14 0.05 above is 163.627 . The role of the quality of budget and budgetary control that influence organizational effectiveness in the provincial city administration has been shown by the evidence that the factors contained in the variable quality of budget and budgetary control is able to significantly positively encourages the creation of organizational effectiveness . If an increase in the quality and budget control simultaneously ( concurrently ) it will improve organizational effectiveness indicators Jambi city government. Key words: Quality Budget , Budgetary Control and Organizational Effectiveness